2020
DOI: 10.5336/healthsci.2019-66106
|View full text |Cite
|
Sign up to set email alerts
|

How Do Midwifery Students Know Our Second Metabolic Organ?

Abstract: İnsanoğlunun, yaşamını sürdürmek için çevresiyle sürekli etkileşim içinde olması gerekmektedir ve mikroorganizmalar bu çevre içinde oldukça önemli bir yer tutmaktadır. 1 Doğumdan itibaren insan vücudu çoğunluğunu bakterilerin oluşturduğu man-tar, virüs ve protozoonları içeren mikrobiyal bir popülasyon barındırmaktadır. İnsan ve mikrobiyal popülasyon arasındaki ilişki temelde, insan vücudunun zarar gördüğü (patojen organizmalar) ve herhangi bir zarar görmediği hatta yarar sağladığı durum (flora)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The microbiota knowledge mean score of the students was found to be 34.63±31.38, and the difference in knowledge mean scores between 4th grade students and other grades was statistically signi cant. Researchers reported that midwifery students should increase their knowledge of intestinal microbiota 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota knowledge mean score of the students was found to be 34.63±31.38, and the difference in knowledge mean scores between 4th grade students and other grades was statistically signi cant. Researchers reported that midwifery students should increase their knowledge of intestinal microbiota 9 .…”
Section: Discussionmentioning
confidence: 99%